Organizational culture and identity unity and division at work - Parker, Martin 1962- (SAGE, 2000)
Examining culture in organizations, Martin Parker discusses its influences on individuals and its uses as a management tool. He presents organisational cultures as 'fragmented unities' in which members feel both part of a collective and individual.